Traditions of social prevention in the activities of the Polish sports organizations. Selected aspects - Piotr Kędzia (Journal of Education, Health and Sport, 2018)
The analysis of the first Polish sports organizations indicate their multi-faceted contexts of social prevention. The most important of them can include: preventing factors that threaten health, the fight against illiteracy, social deviated prevention, prevention of violence and xenophobia stadiums and initiating preventive measures in defence of Poland. Preventive actions taken were aimed at not only securing proper psychophysical development of members of associations, but also expressed concern for the common good. Implemented by sports organizations preventive actions have a profound pedagogical dimension. Their main imperative was to take responsibility for the future of the young generations of Poles.